Investigation of taper angle in dry micro wire EDM - Ali, Mohammad Yeakub; Banu, Asfana; Shaffiq, Muhammad; Abd. Rahman, Mohamed; Konneh, Mohamed; Salehan, Muhammad (International Journal of Mechanical Engineering and Robotics Research, 2018)
Dry micro wire EDM have been introduced to fabricate complex micro parts with high accuracy. It is a process where gas is used instead of liquid as the dielectric fluid. However, in order to achieve high accuracy, taper angle remains as one of the critical issues. Hence, this paper investigates the effect of process parameters; gap voltage and wire tension; on taper angle in dry micro wire EDM on stainless steel using compressed air as dielectric fluid and tungsten as wire electrode. Empirical model using general factorial method was developed for the estimation of taper angle. Based on the ANOVA, gap voltage has major influence on taper angle. The optimum machining parameters for minimum taper angle were found to be 85 V gap voltage and 14 % wire tension.